Six Decades of Energy Poverty: Reducing Disparities in Latin America and the Caribbean? - González, Fernando Antonio Ignacio; Ibáñez-Martín, María María (Revista INVI, 2023)
Latin America and the Caribbean are one of the most unequal regions in the world, with high levels of poverty and reduced state capacity to solve structural problems. In this paper, we examined the existence of a β-convergence process between countries (i.e., reduction of disparities) in terms of energy poverty indicators. For this, we construct an annual panel of countries for the last six decades and for thirteen energy poverty indicators covering three dimensions (access, quality, and affordability). The results indicate that a convergence process has taken place between countries of Latin America and the Caribbean, which includes all the dimensions analyzed (i.e., the countries of the region have become more similar in terms of energy poverty over time). Context-specific recommendations that emerge from the findings aim at promoting greater adoption of renewable energy, reducing delays in obtaining an electricity connection, and cutting subsidies for natural gas and oil.